Os (des)caminhos da agroenergia na Bahia: a participação da MRG de Irecê no circuito espacial produtivo do agrodiesel / The paths of the Bahia bioenergy: MRG of Irecê participation in the fuel farm productive SPA TIAL CIRCUIT - Leandro Pessoa Vieira (Sociedade & Natureza)
he aim of this article is to analyze what reason the castor cultivation is returning to Geographic Microregion (MRG) Irecê, in other words, understand why the the castor cultivation.Firstly, the analysis of regulatory framework that encourages the cultivation of castor in Brazil. Then the goal is to identify the argumentative techniques employed by supranational institutions on global warming, as studies published by these institutions are some of the scientific references to support the creation of regulatory frameworks as PNPB. Finally, we seek to highlight the consequences of discourses and inter-actions, forming the productive spatial circuit, that are impacting the intensification of ricinocultura on farms in the study area.